2006
DOI: 10.1080/00107510701244055
|View full text |Cite
|
Sign up to set email alerts
|

The modified Newtonian dynamics—MOND and its implications for new physics

Abstract: No more salient issue exists in contemporary astrophysics and cosmology than that of the elusive "dark matter". For many years already Milgrom's paradigm of modified Newtonian dynamics (MOND) has provided an alternative way to interpret observations without appeal to invisible dark matter. MOND had been successful in elucidating economically the dynamics of disk galaxies of all scales, while doing less well for clusters of galaxies; in its original form it could not address gravitational lensing or cosmology. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
138
1
10

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(152 citation statements)
references
References 76 publications
3
138
1
10
Order By: Relevance
“…On the other hand, some researchers (see e.g. Bekenstein 2006 and references therein) claim that the Pioneer anomaly can be explained by the MOND hypothesis. This assumption can prove wrong if uneven thermal radiation in the spacecrafts is found (Toth & Turyshev 2009), which could possibly come from the flyby anomaly (Turyshev 2009).…”
Section: A Particular Form Of the Interpolating Function In The Mond mentioning
confidence: 99%
“…On the other hand, some researchers (see e.g. Bekenstein 2006 and references therein) claim that the Pioneer anomaly can be explained by the MOND hypothesis. This assumption can prove wrong if uneven thermal radiation in the spacecrafts is found (Toth & Turyshev 2009), which could possibly come from the flyby anomaly (Turyshev 2009).…”
Section: A Particular Form Of the Interpolating Function In The Mond mentioning
confidence: 99%
“…Low-energy effective field theories have been rejected when, despite having Lorentz-invariant Lagrangians, they admit superluminal fluctuations [5]. Subluminal propagation of field fluctuations has been imposed as a condition on a relativistic gravitation theory for the MOND paradigm [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The modified Newtonian dynamics is discussed [6] as an alternative to the proposed existence of dark matter which should comprise about 23% of the Universe mass. On the other hand, if it is granted that the most realistic according to astrophysics, cold, dark matter exists in nature, the question arises as to what are its constituents.…”
mentioning
confidence: 99%
“…Equations (4) and (5) were substituted in inequality (6). It was shown that the strongest constraints follow at the shortest separation a = 235 nm.…”
mentioning
confidence: 99%